2019
DOI: 10.3390/land8100147
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Environmental Amenities across Space: A Geographically Weighted Regression of Housing Preferences in Greenville County, SC

Abstract: As global consumption and development rates continue to grow, there will be persistent stress placed on public goods, namely environmental amenities. Urban sprawl and development places pressure on forested areas, as they are often displaced or degraded in the name of economic development. This is problematic because environmental amenities are valued by the public, but traditional market analysis typically obscures the value of these goods and services that are not explicitly traded in a market setting. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…In addition, other studies focused on grass cover reported a positive effect of proximity to the nearest moderate grassland area within 800 m of the property [ 19 ] and parcel and neighborhood irrigated grassland [ 34 , 42 ] on housing prices, while non-irrigated grass cover on the property had a negative effect on house prices [ 42 ]. Residents’ high horizontal view of green vegetation within minutes [ 60 ], 400 m [ 61 ], 160.9 m [ 62 ], 253 m [ 63 ] of the property were also reported to have positive effects on residential property values. Likewise, proximity to a national park had a positive effect on housing prices [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other studies focused on grass cover reported a positive effect of proximity to the nearest moderate grassland area within 800 m of the property [ 19 ] and parcel and neighborhood irrigated grassland [ 34 , 42 ] on housing prices, while non-irrigated grass cover on the property had a negative effect on house prices [ 42 ]. Residents’ high horizontal view of green vegetation within minutes [ 60 ], 400 m [ 61 ], 160.9 m [ 62 ], 253 m [ 63 ] of the property were also reported to have positive effects on residential property values. Likewise, proximity to a national park had a positive effect on housing prices [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the reviewed studies focused implicitly and/or explicitly on evaluating how recreation and aesthetic (cultural) services of urban forest types in neighborhoods influenced residential property values. Examples of such studies reported positive effects of resident green viewshed from windows [ [60] , [61] , [62] , [63] , 105 ] and proximity to urban forests types for hiking, biking, jogging, exercising, observing plants and animals [ 19 , 24 , 55 , 69 , 106 , 107 ] on housing prices. Urban forests also have direct health benefits to residents relating to improvement in psychological, emotional, physical, and mental health of urban residents [ 1 ].…”
Section: Discussionmentioning
confidence: 99%